2015
DOI: 10.1016/j.ijrobp.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Tumor Cell Death After High-Dose Hypofractionated Irradiation: Implications for Stereotactic Body Radiation Therapy and Stereotactic Radiation Surgery

Abstract: Summary In experimental mouse tumors, high-dose irradiation in a single fraction caused progressive increase in tumor cell death in 2 to 5 days. Such delayed tumor cell deaths appeared to be due to radiation-induced deterioration of intratumor microenvironment characterized by profound reduction of blood perfusion and increase in hypoxia. Similar secondary and indirect cell death may play an important role in clinical stereotactic body radiation therapy and stereotactic radiation surgery. Purpose The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 34 publications
6
108
1
2
Order By: Relevance
“…[59][60][61] Recent studies have suggested that this may be an important factor in the response of tumours to SBRT. 62 These observations are consistent with the concept that acutely hypoxic cells and/or the larger number of cells that are partially resistant to irradiation due to being at intermediate oxygen levels in tumours may in fact represent a more important population of cells relevant to tumour control effected by standard fractionated radiation therapy rather than the most hypoxic cell populations. 63 However, despite the overwhelming data that many tumours contain hypoxic cells and the findings that levels of hypoxia in various tumour types are predictive of treatment outcome, approaches to addressing this issue in radiation therapy treatment of patients have had only limited success.…”
Section: Role Of Hypoxiasupporting
confidence: 87%
“…[59][60][61] Recent studies have suggested that this may be an important factor in the response of tumours to SBRT. 62 These observations are consistent with the concept that acutely hypoxic cells and/or the larger number of cells that are partially resistant to irradiation due to being at intermediate oxygen levels in tumours may in fact represent a more important population of cells relevant to tumour control effected by standard fractionated radiation therapy rather than the most hypoxic cell populations. 63 However, despite the overwhelming data that many tumours contain hypoxic cells and the findings that levels of hypoxia in various tumour types are predictive of treatment outcome, approaches to addressing this issue in radiation therapy treatment of patients have had only limited success.…”
Section: Role Of Hypoxiasupporting
confidence: 87%
“…A significant increase in tumor oxygenation was observed by 19 F MRI in Dunning prostate AT1 tumors up to 10 hours after 20 Gy irradiation [50] and by EPR in RIF-1 tumors, 72–120 hours after 20 Gy [24]. Meanwhile, a recent study in FSaII tumors demonstrated secondary cell death, based on clonogenic survival assays 2–5 days, after 20 Gy, attributed to by vascular damage, which was accompanied by a significant increase in hypoxic markers [55]. As levels of hypoxia and response are expected to vary with radiation dose, tumor type, host species and method of anesthesia the need for further investigations is obvious.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Some argue that the linear-quadratic model provides an adequate representation of the doseresponse relationship at high doses and that observed clinical outcomes are entirely consistent with the predictions of this model. [11][12][13] Others assert that radiobiologic mechanisms, such as profound vascular damage 14,15 and antigen expression, different from classic DNA damage, are evoked above a threshold dose of [8][9][10][11][12] Gy and that the high levels of tumor control observed in radiosurgery reflect this "new radiobiology" and enhanced dose-response 13,[16][17][18] Fig. 2).…”
Section: Radiobiologic Rationale For Hypofractionated Versus Singlefrmentioning
confidence: 99%